Health Education on Dengue Hemorrhagic Fever (DHF) for Disease Transmission Prevention: DHF Health Education - Suwardha Yunus; Irawati Anwar; Iwan (Journal of Evidence-Based Community Health, 2025)
Dengue Hemorrhagic Fever (DHF) remains a significant public health concern in tropical countries such as Indonesia, particularly during the rainy season. Early education and awareness are crucial in minimizing morbidity and mortality caused by the disease. This community engagement activity aimed to improve knowledge and awareness among patients, families, and visitors at UPT RSUD Labuang Baji Makassar regarding the prevention and early identification of DHF. The program involved structured health education sessions using a Satuan Acara Penyuluhan (SAP) plan, which included presentations, discussions, and distribution of educational materials such as posters and leaflets. The sessions were conducted in inpatient wards, engaging patients and their families. The intervention enhanced participants’ understanding of DHF symptoms, transmission, critical phases, and preventive measures such as maintaining environmental hygiene, proper water management, and promoting healthy behaviors. Increased motivation among family members was observed in taking part in preventive actions at home and in their communities. Health education efforts targeting both patients and their families are effective in raising awareness and promoting behavioral changes for DHF prevention. Continuous collaboration between healthcare providers and the community is essential to sustain preventive measures and reduce the incidence of DHF.